Numerical solutions of the forced perturbed Korteweg-de Vries equation with variable coefficients - Kim, Gaik Tay; Yaan, Yee Choy,; Wei, King Tiong; Chee, Tiong Ong; Nazatulsyima, Mohd Yazid (Academic Publications, Ltd., 2017)
In this paper, we solved the forced perturbed Korteweg-de vries (FpKdV) with variable coefficient arises in nonlinear wave propagation in an elastic tube filled with a sym- metrical stenosis filled with a viscous fluid by two numerical methods, namely method of lines and pseudospectral method. We then compared both numerical solution with its progressive wave solution. Both methods solve FpKdV equation with maximum absolute errors of 10-2.